2017
DOI: 10.1021/acs.jced.7b00650
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Measurement of Dynamic Viscosity and Density of n-Alkanes at High Pressures

Abstract: New experimental data of the dynamic viscosity and density of pentane, octane, nonane, decane, and dodecane are reported. The experimental method was validated by determining and comparing the dynamic viscosity and the density of decane with the data previously published in the international literature, obtaining a maximum deviation of 12 μPa·s and 0.35 kg·m–3 for dynamic viscosity and density, respectively. The measurements were performed simultaneously using a capillary tube viscometer and a vibrating tube d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 44 publications
0
29
0
Order By: Relevance
“…Pressure transducers and platinum probes were calibrated, and the combined uncertainties were estimated to be u c (P) = 0.002 MPa and u c (T) = 0.009 K. For details about the method and procedure used, the reader is referred to the previous works. 29,30 Measurements of dissociation conditions of gas hydrates were performed in an experimental apparatus designed and built in house, consisting of a synthetic nonvisual apparatus. The equilibrium cell is "blind" and made of stainless steel.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Pressure transducers and platinum probes were calibrated, and the combined uncertainties were estimated to be u c (P) = 0.002 MPa and u c (T) = 0.009 K. For details about the method and procedure used, the reader is referred to the previous works. 29,30 Measurements of dissociation conditions of gas hydrates were performed in an experimental apparatus designed and built in house, consisting of a synthetic nonvisual apparatus. The equilibrium cell is "blind" and made of stainless steel.…”
Section: Methodsmentioning
confidence: 99%
“…Viscosity data of polar and nonpolar fluids are of great importance for several technological applications and in chemical engineering mainly where the movement of the fluids controls the process. 29,30 In the literature, several experimental methods Gas Hydrate Dissociation Conditions. In the oil industry, the formation of gas hydrates is considered as a potential to cause operational problems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…25,27,28 However, the uncertainty of viscosity data can be increased by increasing the system temperature. 30,31 Taking into account the contributions mentioned, the combined expanded uncertainties with 0.95 level of confidence (k ≈ 2) in the density and viscosity are estimated to be U c (ρ) = 0.0007 g•cm −3 and U c (η) = 0.01 mPa•s, respectively.…”
Section: Materials and Measurementsmentioning
confidence: 99%
“…To calculate the uncertainties for experimental data, different factors such as density, viscosity, temperature, and pressure of the system, the accuracy of the balance and the viscometer–densimeter apparatus, and the impurity of the tested samples were implemented. For compounds with purity above 99%, studies in the literature have shown that the effect of the impurity in the uncertainty of density data is ignored. However, the relative uncertainty in density data for samples with a purity of 99% or less increases by 0.1%. , The uncertainty in viscosity data is most affected by the amount of water added to the sample. ,, However, the uncertainty of viscosity data can be increased by increasing the system temperature. , Taking into account the contributions mentioned, the combined expanded uncertainties with 0.95 level of confidence ( k ≈ 2) in the density and viscosity are estimated to be U c (ρ) = 0.0007 g·cm –3 and U c (η) = 0.01 mPa·s, respectively.…”
Section: Materials and Measurementsmentioning
confidence: 99%